Towns, townships and villages of Lithuania: their demographical and urban changes influence to the identity of the countries landscape spatial structure - Dringelis, Liucijus (Journal of Architecture and Urbanism, 2013)
In the last decades, globalization and integration processes are going very intensively. They bring together nations, their cultures, but in the same time gradually disappear national identity. This process touches a lot of spheres, but especially big influence has to the condition of countries towns, townships and villages, their demographics, urbanity, architecture and landscape that in some scale gradually looses their visual aesthetic identity and singularity. So saving and cherishing characteristics of countries landscape, spatial structure character of living places and natural surroundings in the conditions of globalization is really actual problem. The aim of this article is to give data about countries living system and demographical situation changes that is based on Lithuanian Statistics Department 2001 and 2011 made general country population and dwelling census statistics that predetermines countries towns, townships and villages landscape spatial structure character and its identity. Mentioned analysis showed, that during 2001-2011, number of country residents decreased by 440,37 thousands or 12,64 percent. In such way, during this period decreased number of towns (was 106, now – 103), number of villages (was 19842, now – 19004) and number of individual farms (was 1735, now – 1687). Also, from current number of villages or individual farms, about 18 percent of villages and 52 percent of individual farms don’t have residents and are near to the limit of disappearance. Mentioned demographical and urban changes undoubtedly makes influence to Lithuanian towns, townships and villages landscape spatial structure singularity and identity. This singularity, as very important part of national cultural heritage, can be saved only solving economical, juridical and professional questions complexly. Article in Lithuanian. Lietuvos miestai, miesteliai ir kaimai: jų urbanistinių ir demografinių pokyčių įtaka šalies kraštovaizdžio erdvinės struktūros savitumui Santrauka. Pastaraisiais dešimtmečiais pasaulyje gana intensyviai vyksta globalizacijos ir integracijos procesai, kurie suartina tautas, jų kultūras, tačiau kartu palaipsniui nyksta tautų tapatumas, prarandamas tautinis identitetas. Šis procesas paliečia daugelį sričių, tačiau ypač didelę įtaką turi šalies miestų, miestelių ir kaimų būklei, jų demografijai, urbanistikai, architektūrai, kraštovaizdžiui, kurie tam tikru mastu palaipsniui praranda savo vizualinį estetinį identitetą, savitumą. Todėl išsaugoti ir puoselėti šalies kraštovaizdžio savybes, gyvenamųjų vietovių erdvinės struktūros pobūdį bei gamtinę aplinką globalizacijos sąlygomis yra labai aktuali problema. Šio straipsnio tikslas yra, remiantis Lietuvos statistikos departamento 2001 ir 2011 m. visuotinio šalies gyventojų ir būstų surašymo rezultatų statistine analize, pateikti duomenis apie šalies apgyvendinimo sistemos bei demografinės situacijos pokyčius, kurie lemia šalies miestų, miestelių ir kaimų kraštovaizdžio erdvinės struktūros pobūdį, jos savitumą. Minėta analizė parodė, kad per 2001–2011 m. laikotarpį gyventojų skaičius šalyje sumažėjo 440,37 tūkst. arba 12,64 proc. Taip pat per šį laikotarpį atitinkamai sumažėjo miestų (buvo 106, dabar – 103) bei itin sumažėjo kaimų (buvo 19 842, dabar – 19 004) ir viensėdžių (buvo 1735, dabar – 1687). Be to, iš dabar esančio kaimų ir viensėdžių skaičiaus apie 18 proc. kaimų ir apie 52 proc. viensėdžių neturi gyventojų ir yra prie išnykimo ribos. Minėti demografiniai ir urbanistiniai pokyčiai neabejotinai daro įtaką Lietuvos miestų, miestelių ir kaimų kraštovaizdžio erdvinės struktūros savitumui, jo identitetui. Šis savitumas, kaip labai svarbi tautos kultūros paveldo dalis, gali būti išsaugotas tik kompleksiškai sprendžiant ekonominius, juridinius bei profesinius klausimus. Reikšminiai žodžiai: miestai, miesteliai, kaimai, kraštovaizdis, urbanistika, demografija, statistika, savitumas.